Task- Based Language Teaching TBLT in Improving Students’ Speaking Proficiency - Marhaeni Sabil (Universitas Sulawesi Barat, 2020)
This article explores about the use of Task-Based Language Teaching can improve the speaking proficiency students of class XII IPA SMAN 1 Amali Kabupaten Bone. The research method was used is Experimental design. The populations were 350 students of SMAN 1 Amali Bone and samples were 50 students, purposive sampling was the technique in taking sample. Data on students’ speaking were collected in line with the instrument (test and questionnaire) and analyzed by inferential statistic. Based on the research findings and discussion, the conclusions are: 1) The use of Task- Based Language Teaching (TBLT) in teaching speaking class can improve the students’ speaking skill. It was proved by the mean score of the students’ posttest in experimental group was 79. 69 and the mean score of the students’ posttest in discussion technique was 73.85. it means that there was higher improvement in experimental class; 2) The students are interested in learning speaking English through Task- Based Language Teaching (TBLT). The mean score of students’ interest was 92.0 %. It was classified as very high interest.